Spatial Distribution and Cluster Analysis of Dengue In Tamil Nadu, India 2017 – 2019 - Sundaram, Senthil Kumar; Thirunaaukarasu D; Tejas J; Somasundaram A; Sampath P (National Journal of Community Medicine, 2023)
Background: Dengue, a viral infectious disease, is constantly reemerging and is spread by mosquitoes. It is most common in tropical and subtropical areas of the world, particularly in the Asia-Pacific region. A Surveillance study was carried out in the state of Tamil Nadu-India, from 2017 to 2019 to better understand the epidemiology and geographic spread of dengue. Materials & Methods: Geographical information system (GIS) software was used to map the district-wise endemicity. To pinpoint dengue hotspots and coldspots, spatial statistical analysis techniques like Getis-Ord Gi* were used. To comprehend the endemicity and clustering patterns in the state, self-organising maps (SOM)was also used. Results: Dengue hotspots are Chennai, Thiruvallur, Kancheepuram and cold spots are Cuddalore and Ariyalur for across three years. The SOM divides 30 districts into six clusters. The 10 districts are identified as extremely high endemic cluster and 9 districts as very high endemic cluster. These SOM clusters were projected geographically, and the districts were divided based on the intensity of the cases. Conclusion: SOM-GIS, a visualization technique, identifies hot spots and endemic clusters which helps in prompt decision-making for disease management by public health personnel.